(untitled) (Semiárida, 2023)
The La Picasa lake valuable grassland Area is one of the few remaining natural grasslands in the south of the Santa Fe province, where elements of grassland halophyte flora are combined with brackish lakes, becoming a reservoir of plant genetic resources for this type of environment. The objective of this work was to carry out a phenological survey of the flora of beekeeping and ornamental interest in the area, which serves as a reference for these activities. Forty-six species of beekeeping interest and 19 species of ornamental interest were found, most of them native. The best represented family was Asteraceae. The flowering contribution covers the September-April period, with a peak towards the end of December and the beginning of January. The knowledge of these species and their flowering time presented here, constitutes an important tool for the planning, project and management of beekeeping and landscape